2013
DOI: 10.1002/pon.3392
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive processing in relation to psychological distress in women with breast cancer: a theoretical approach

Abstract: The results did not provide support for Creamer's model in an early-stage breast cancer population, which suggests that early-stage breast cancer patient's process trauma differently from late-stage cancer patients. Therefore, it might be suggested that early-stage and late-stage cancer patients require different types of support and treatment for the distress experienced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 35 publications
5
5
0
4
Order By: Relevance
“…Posttraumatic growth mediated the connections of perceived social support to quality of life and to depressive symptoms . No evidence was found in support of the mediating role of avoidance of thinking about cancer and related thoughts in explaining the relationship between intrusion and psychological distress …”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Posttraumatic growth mediated the connections of perceived social support to quality of life and to depressive symptoms . No evidence was found in support of the mediating role of avoidance of thinking about cancer and related thoughts in explaining the relationship between intrusion and psychological distress …”
Section: Resultsmentioning
confidence: 90%
“…One study found that perceptions of a lack of decisional control predicted more psychological distress but only when coping strategies and baseline levels of psychological distress were not entered in the analysis. One study did not find any association between rumination and psychological distress …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…These considerations are important to the planning and administration of supportive or survivorship care, which has been advocated at the end of treatment or within three months post-treatment. Undue distress or even increasing distress may be allowed if healthcare providers delay the identification of problems and the creation of a care plan intended to prevent or ameliorate distress (Rissanen et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…The number of psychological comorbidities and the survivor's time point in the cancer trajectory may determine her level of distress and should inform the timing and type of intervention (Rissanen, Arving, Ahlgren, Cernvall, & Nordin, 2014). Adjustment disorders, anxiety, grief, and mood swings were common causes of psychological distress in survivors (Mitchell et al, 2011).…”
Section: Introductionmentioning
confidence: 99%